Impacto del gasto público en educación en la desigualdad medida por ingresos - Peñaherrera Plúa, María Gabriela (2019)
In recent years, the reduction of income inequality became a priority in the agendas of governments and multilateral organizations. Both, the theory and the empirical evidence confirm that education is a strategic determinant to achieve an equitable distribution of income, while improving the social and economic conditions of a country. In 2015, the United Nations Educational, Scientific and Cultural Organization (UNESCO) proposed a range of investment in public spending on education of between four and six percentage points of the Gross Domestic Product (GDP). This study examines through a panel of data from 26 countries in the period 1990-2016, whether this minimum level in public spending on education of four percentage points is a determining element to reduce income inequality. The findings indicate that a higher spending on public education implies a more equal distribution of income.